British Exhibition Art 6'75 Basel. - Kunstbeurs Basel (London : The Society of London Art Dealers, 1975)
Auerbach, Frank ; Bacon, Francis ; Blake, Peter ; Buckley, Stephen ; Burra, Edward ; Caro, Anthony ; Caulfield, Patrick ; Cohen, Bernard ; Davies, John ; Denny, Robyn ; Flanagan, Barry ; Freud, Lucian ; Gilbert & George ; Green, Alan ; Green, Anthony ; Hall, Nigel ; Hamilton, Richard ; Hepworth, Barbara ; Hill, Anthony ; Hockney, David ; Hodgkin, Howard ; Hoyland, John ; Jones, Allen ; King, Phillip ; Kitaj, R.B. ; Martin, Kenneth ; Martin, Marty ; Milow, Keith ; Moore, Henry ; Nicholson, Ben ; Paolozzi, Eduardo ; Pasmore, Victor ; Priest, Margaret ; Riley, Bridget ; Scott, Tim ; Scott, William ; Self, Colin ; Smith, Jack ; Smith, Richard ; Sutherland, Graham ; Tindle, David ; Tucker, William ; Walker, John
geboortedata per kunstenaar
British Exhibition Art §'75 Basel, Schweizer Mustermesse Basel, 18.6.75 - 23.6.75
Engels
boek
Keywords: Groot-Brittannië